1996
DOI: 10.1080/10934529609376522
|View full text |Cite
|
Sign up to set email alerts
|

In situ solidification of an industrial sludge lagoon: Laboratory studies and field activities

Abstract: An industrial sludge lagoon is being closed through in situ addition and mixing of Portland cement, followed by on-site vaulting. The sludges must be solidified in order to enhance the physical properties and to facilitate handling and vaulting. The solidified materials must gain enough compressive strength so that heavy tracked equipment can continue operation on it and for successful construction of a vault and cap. Laboratory investigations were carried out in order to determine a process control strategy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…It is widely acknowledged that solidification decreases the water content of the sludge and enhances its strength by constructing a skeleton structure [7,[14][15][16][17][18]. Legiec et al [19] solidified an industrial sludge lagoon and tested the in situ solidified sludge and found that the unconfined compressive strength of the solidified sludge with a water content of 150% reached 206.80 kPa by mixing it with 22% of Portland cement. From a throughout analysis of the different sludge treatment methods, the vacuum preloading reduced the water content of sludge but did not obviously improve its strength.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely acknowledged that solidification decreases the water content of the sludge and enhances its strength by constructing a skeleton structure [7,[14][15][16][17][18]. Legiec et al [19] solidified an industrial sludge lagoon and tested the in situ solidified sludge and found that the unconfined compressive strength of the solidified sludge with a water content of 150% reached 206.80 kPa by mixing it with 22% of Portland cement. From a throughout analysis of the different sludge treatment methods, the vacuum preloading reduced the water content of sludge but did not obviously improve its strength.…”
Section: Introductionmentioning
confidence: 99%
“…Η ενυδάτωση των C3S και C2S, η ποσότητα των οποίων είναι κατά προσέγγιση 75% κατά βάρος, έχει ως αποτέλεσμα την ανάπτυξη της αντοχής του τσιμέντου μετά την αρχική πήξη. [Conner 1993] Πίνακας 1.1: Βασικές Αντιδράσεις Ενυδάτωσης [Πηγή: Weitzman 1990, Legiec 1996 Αντιδρώντα Προϊόντα Εκλυόμενη θερμότητα (cal/g) [Young 1972, Birchall & Thomas 1984, Conner 1990, Conner 1993, Wang et al 1994, Shi & Day 1996 1.6.1.1 Διερνασίες Σ/Σ με γρήση Τσιμέντου Πόοτλαντ [Bishop et al 1983, Bishop et al 1984, Perry & Clarke 1985, Chino «Sc Kawamura 1988, Claudio & Sobrinho 1990, Claudio 1991, Montgomery et al 1991b, Pollard et al 1991, McWhinney & Cocke 1993, Hinsenveld & Bishop 1994 To Υψικαμίνου) [Grutzeck et al 1985, Myers et al 1985, Hester 1987, Yadana et al 1987, Weitzman et al 1988, Wentz et al 1988, Rushbrook et al 1989, Razzell 1990, Roy et al 1991, Hills et al 1992a, Rinehart et al 1993, Akram et al 1994, Shi&Day 1995b Η ιπτάμενη τέφρα και η σκόνη υψικαμίνου τσιμέντου προσδίδουν στο μπετόν χαμηλότερο κόστος αφού μπορούν να αντικαταστήσουν το 25-35% του τσιμέντου χωρίς καμμιά επίδραση στην αντοχή σε θλίψη [Malhotra 1993 [Andres & Irabien 1994a, Andres & Irabien 1994b, η σκόνη κονιοποιημένου καυσίμου (Pulverised Fuel Ash -PF A)…”
Section: ί ' 'unclassified